Improved Simulation of ENSO Variability Through Feedback From the Equatorial Atlantic in a Pacemaker Experiment. Issue 2 (18th January 2022) - Bi, Daohua; Wang, Guojian; Cai, Wenju; Santoso, Agus; Sullivan, Arnold; Ng, Benjamin; Jia, Fan
Abstract: The tropical Pacific Ocean interacts with the tropical Atlantic Ocean on interannual time scales. However, most coupled climate models misrepresent and/or underestimate these teleconnections, which have important implications on the periodicity of the El Niño‐Southern Oscillation (ENSO). Imposing the observed sea surface temperature over the tropical Atlantic from 1970 onwards, a pacemaker experiment is constructed using the second version of the Australian Community Climate and Earth System Simulator Coupled Model (ACCESS‐CM2). Compared with control runs which reasonably simulate the interaction between ENSO and the north tropical Atlantic variability, the pacemaker experiment significantly improves the impact of the Atlantic Niño/Niña on ENSO. This enhanced teleconnection contributes to a more realistic ENSO periodicity compared with the control runs, thus suggesting that capturing the influence from equatorial Atlantic variability is important for an improved ENSO simulation. Plain Language Summary: The El Niño‐Southern Oscillation (ENSO) is one of the most important drivers of extreme weather and climate events on Earth. Achieving a realistic ENSO, which is critical for accurate climate predictions and projections, has been a challenge for many climate models. For example, the ACCESS‐CM2, one of the latest state‐of‐the‐art climate models contributing to the sixth IPCC report, is found to only generate a quasi‐biennial ENSO, failing to reproduce the observed dominant 3–7 year periodicities. Here, we show that the problem is at least partly due to the model's persistent and extensive tropical Atlantic warm bias. Replacing the tropical Atlantic SST with the observed over the course of 50‐year simulation results in a more realistic ENSO variability. This result suggests that equatorial Atlantic variability plays an important role in shaping Pacific ENSO events. Improving the model's representation of the tropical Atlantic is therefore crucial for enhancing its skill in ENSO simulation, prediction, and projection. Key Points: ACCESS‐CM2 displays warm biases in the eastern tropical Pacific and Atlantic oceans and simulates an overly strong biennial ENSO Pacemaker experiments with observed sea surface temperature (SST) imposed over the tropical Atlantic improve ENSO frequency Realistic representation of SST over the tropical Atlantic is crucial for enhancing the model's skill in simulating ENSO property